THE IMPACT OF CENTRAL BANK DIGITAL CURRENCIES ON MONETARY POLICY AND FINANCIAL STABILITY - Judijanto, Loso (Penelitian dan Pengembangan Ilmu, 2025)
The development of Central Bank Digital Currencies (CBDCs) has become a major focus in efforts to transform the global financial system. On the one hand, CBDC is expected to be able to encourage the expansion of financial access (financial inclusion), but on the other hand, its presence has the potential to pose risks to financial system stability (financial stability). This research aims to explore and analyze the trade-off between financial inclusion and financial stability in the context of CBDC implementation. Using a Systematic Literature Review (SLR) approach, this research examines 58 selected articles published in the 2020-2024 period, originating from reputable databases such as Scopus, Web of Science, and Springer. The research results found that there were two main dimensions of trade-off, namely the benefits of expanding financial access and potential risks to financial stability. These findings were interpreted further in the development CBDC Trade-off Model which theoretically provides a new conceptual framework in understanding the policy implications of CBDC. Practically, this model can be used as a reference for regulators and monetary authorities in designing a CBDC implementation strategy that is balanced between encouraging financial inclusion and maintaining financial system stability. This research also recommends further empirical-based studies to test the validity of the model in the context of developing and developed countries.